(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
objective of the research to develop a proposed model for the use of lean accounting and target cost in the Kufa cement plant to reduce costs as they are among the most important techniques of strategic cost management in the field of cost accounting and management accounting, The research was conducted on kufa cement factory data to show the effect of using lean accounting techniques and target costing to reduce costs. The research was built on a main hypothesis that the use of lean accounting techniques and target costing leads to reducing costs in the kufa cement factory in manner that is commensurate with the requirements of the modern manufacturing environment. The research reached a number of conclusions, the most important of which is that the techniques of lean accounting and target costing are among the important techniques that reduce costs in the life cycle of the product, from the planning stage to research and development, without compromising the quality of the product. The research reached came out with a number of recommendations, including the necessity of moving the kufa cement factory to the two techniques of lean accounting and target costing, due to the multiplicity of needs and desires of customers and change in benefits and from of products, as well as their role in reducing costs.